2021
DOI: 10.3390/pr9122105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Maturity and Greenhouse Gas Emission in Co-Composting of Chicken Manure with Tobacco Powder and Vinasse/Mushroom Bran

Abstract: This study investigated the effects of different proportions (0%, 5%, 10%, 15%) of bulking agent (vinasse, mushroom bran, and tobacco powder) on maturity and gaseous emissions in chicken manure composting. The results showed that all of the treatments reached the standard of harmless disposal. With the exception of the control treatment, the CH4, N2O, and NH3 emissions in the treatments that had been prepared using the addition of mixed bulking agents were effectively reduced by 2.9–30.6%, 8.30–80.9%, and 37.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Spent mushroom substrate (SMS) and poultry waste stand as formidable allies in the battle against greenhouse gas emissions and environmental degradation. These organic resources hold immense promise, finding effective utilization avenues in composting processes, biogas production, and precision nutrient management strategies [59][60][61]. By redirecting these valuable waste streams away from landfills and harnessing their inherent attributes, we can take substantial strides towards sustainable waste management, climate change mitigation, and the promotion of a more robust ecosystem.…”
Section: Renewable Energy and Gas Emissionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spent mushroom substrate (SMS) and poultry waste stand as formidable allies in the battle against greenhouse gas emissions and environmental degradation. These organic resources hold immense promise, finding effective utilization avenues in composting processes, biogas production, and precision nutrient management strategies [59][60][61]. By redirecting these valuable waste streams away from landfills and harnessing their inherent attributes, we can take substantial strides towards sustainable waste management, climate change mitigation, and the promotion of a more robust ecosystem.…”
Section: Renewable Energy and Gas Emissionsmentioning
confidence: 99%
“…By redirecting these valuable waste streams away from landfills and harnessing their inherent attributes, we can take substantial strides towards sustainable waste management, climate change mitigation, and the promotion of a more robust ecosystem. The utilization of SMS and poultry waste unfolds an opportunity to tackle waste management challenges while concurrently reaping the rewards of environmental enhancement through resource recycling and the generation of renewable energy [59][60][61]. This is especially pertinent considering that these lignocellulosic agro-wastes represent accessible raw biomass that can be harnessed to produce biofuels and bioenergy.…”
Section: Renewable Energy and Gas Emissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chicken manure has become an abundant organic waste with the quick economic development and enhanced demand for food in the world. It is reported that the amount of chicken manure generated will be up to about 457 million tons in 2030 [1]. Because chicken manure is rich in essential and micro-plant nutrients, chicken manure is generally used for increasing soil nutrient content and raising the crop growth by directly returning the chicken manure to the crop [2].…”
Section: Introductionmentioning
confidence: 99%